Structural behaviour and design rules of confined masonry walls: review and proposals - Marques, Rui Filipe Pedreira (2019)
Confined masonry (CM) has been adopted as a cost-effective and earthquake-resistant solution for buildings, mostly in developing countries. CM has large potential for use in Europe, but suitable rules for its application are not available in the European masonry code. This paper presents a critical review of theoretical approaches and experimental investigations on the structural behaviour of CM walls, along with the proposal of simple but suitable design rules. The behaviour to vertical compression and to in-plane shear and bending loadings are comprehensively reviewed with reference to existing studies. Concerning the vertical compressive behaviour, the contribution of each material to the vertical resistance is evaluated and a formulation is proposed. The existing theories for the shear and flexural behaviours are reviewed and the available and new proposed models are compared against experimental results. Finally, requirements for detailing of CM are reviewed from international design codes, in view to propose suitable rules for implementation in a structural code. (C) 2019 Elsevier Ltd. All rights reserved.